Improving the effectiveness of secondary prevention caries in women during pregnancy - Zh. V. Solovyeva; E. S. Zaporozhskaya-Abramova; A. A. Adamchik; T. F. Kosyreva; T. V. Shkirya (LLC "Endo Press", 2020)
Aim. To evaluate the clinical efficacy of long-acting remineralizing medical means in the complex prevention of caries in pregnant women.Materials and methods. The study was conducted on the basis of the Department of Therapeutic Dentistry of the Kuban State Medical University of the Ministry of Health of Russia. A total of 87 people were examined, aged 24 to 37 years, with different levels of oral hygiene 84 patients confirmed their consent to the treatment and prophylactic measures, after which three working groups were formed depending on the long-acting remineralizing agents used "Clinpro-XTVarnish" manufactured by 3MESPE, "Schmelz-versiegelungsliquid" manufactured by HUMANCHEME, "InnoDent Repair" manufactured by InnoDent LLP respectively) and 1 control group. The assessment of the dental status of pregnant women was carried out using indices: CFE, Fedorov-Volodkina oral hygiene index (HI), gingivitis index GI (Loe H., Silness J.).Results. According to the data of a clinical study, it was determined that a high quality oral cavity sanitation with concomitant use of long-acting therapeutic and prophylactic agents increases the effectiveness of preventive measures in pregnant women.Conclusions. The data obtained indicate the achievement of a long-term preventive result, which makes it possible to recommend the investigated fluorine-containing agents for remineralization of hard dental tissues in order to control the state of the oral cavity of women during pregnancy.